INTERACTIVE MULTIMEDIA DESIGN COMPANY PROFILE AND PRODUCT CATALOG AS A PROMOTIONAL MEDIA OF ZIE BATIK SEMARANG - Mubarok, Khafidz Ibnu (Arty: Jurnal Seni Rupa, 2019)
Zie Batik Semarang is a company engaged in the home batik industry with the characteristics of natural dyes. The rapid development of technology requires businesses to think creatively in promoting products offered to be able to penetrate the export market and expand the nameof the company. The way to achieve this goal is to build a relationship with other companies to establish cooperation as business partners, so that Zie Batik can be known in a wider scope. Therefore, digital promotional media in the form of interactive multimedia was chosen to build confidence and trust in the company’s partners. The final goal of this study project is to produce digital promotional media in the form of interactive multimedia that contains company profiles and product catalogs, which are expected to facilitate communication between companies and prospective customers and increase the trust and image of the company in a wider scope. This study project is made through four stages including, preliminary processes, pre-production, production, and post-production. Marketing activities carried out by a company should follow the development of the times so that the communication process runs well and in accordance with the target.